2013
DOI: 10.1177/2050640613504917
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking is a modifiable risk factor for Barrett's oesophagus

Abstract: Background: Cigarette smoking has been associated with an increased risk of oesophageal adenocarcinoma (OAC). However, the impact of smoking and more importantly smoking cessation on Barrett's oesophagus (BO) is unclear. Objective: The aim of the study is to evaluate the association between cigarette smoking and presence of BO in a large prospective cohort of patients with gastro-oesophageal reflux disease (GORD). Methods: Patients presenting to the endoscopy unit for upper endoscopy completed a validated GORD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…Tobacco smoking is associated with higher Barrett esophagus prevalence. In a cohort study of 1056 patients undergoing endoscopy, Barrett esophagus was diagnosed in 12% of people who smoked cigarettes compared with 1.1% of people who did not smoke cigarettes ( P < .001) …”
Section: Evaluating Patients For Barrett Esophagusmentioning
confidence: 99%
See 1 more Smart Citation
“…Tobacco smoking is associated with higher Barrett esophagus prevalence. In a cohort study of 1056 patients undergoing endoscopy, Barrett esophagus was diagnosed in 12% of people who smoked cigarettes compared with 1.1% of people who did not smoke cigarettes ( P < .001) …”
Section: Evaluating Patients For Barrett Esophagusmentioning
confidence: 99%
“…In a cohort study of 1056 patients undergoing endoscopy, Barrett esophagus was diagnosed in 12% of people who smoked cigarettes compared with 1.1% of people who did not smoke cigarettes (P < .001). 10 A systematic review and meta-analysis of 29 cohort studies (24 retrospective and 5 prospective) that included 13 434 patients (mean body mass index range, 39-51.2) undergoing evaluation prior to bariatric surgery reported a pooled prevalence of Barrett esophagus of 0.9% (95% CI, 0.7%-1.3%). This study showed a positive association between mean body mass index and Barrett esophagus prevalence, in which for each 1-point increase in body mass index there was a 0.15% increase in prevalence of Barrett esophagus.…”
mentioning
confidence: 99%
“…The risk factors for Barrett's adenocarcinoma include male gender, increased age, obesity, smoking, long-segment Barrett's esophagus, reflux esophagitis or symptomatic GERD, non-infection of H. pylori, colorectal tumor, and history of dysplasia or adenocarcinoma [3,4,16,17]. Thus, male gender and age constitute common risk Clin J Gastroenterol factors for both diseases, and it can be said that smoking is another commonality due to many reports of a strong causal relationship between smoking and Barrett's adenocarcinoma [18]. Our findings were consistent with the five above-described case reports of simultaneous esophageal SCC and Barrett's adenocarcinoma.…”
Section: Discussionmentioning
confidence: 96%
“…In laboratory examinations, serum squamous cell carcinoma-related antigen was slightly increased (1.9 ng/ml) and H. pylori antibody was negative. During positron emission tomography-CT (PET-CT), 18 Ffluorodeoxyglucose was seen integrated into the thickening of the middle intrathoracic esophageal wall as well as multiple mediastinal lymph node swellings, which suggested esophageal cancer and lymph node metastasis ( Fig. 1).…”
Section: Case Reportmentioning
confidence: 98%
“…Smoking is associated with an increased risk of BE [ 17 , 18 ]. Moreover, the risk of BE increases with higher pack years of cigarette smoking ( p -trend < 0.01) [ 143 ]. Furthermore, the risk of BE decreases with the increasing duration of smoking cessation ( p -trend = 0.01) [ 143 ].…”
Section: Be Preventionmentioning
confidence: 99%